1999
DOI: 10.1093/emboj/18.11.2930
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the human protein kinase CK2 regulatory subunit reveals its zinc finger-mediated dimerization

Abstract: Protein kinase CK2 is a tetramer composed of two α catalytic subunits and two β regulatory subunits. The structure of a C-terminal truncated form of the human β subunit has been determined by X-ray crystallography to 1.7 Å resolution. One dimer is observed in the asymmetric unit of the crystal. The most striking feature of the structure is the presence of a zinc finger mediating the dimerization. The monomer structure consists of two domains, one entirely α-helical and one including the zinc finger. The dimer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
157
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(172 citation statements)
references
References 57 publications
14
157
0
1
Order By: Relevance
“…For p53, the binding region includes the sequence between amino acids 71-149, in the case of DNA Topoisomerase IIa a central region (amino acids 51-110) was implicated and for Nopp 140, the first Nterminal 20 amino acids. This diversity of docking sites on CK2b, which differ from the catalytic centre of the enzyme, may represent a mechanism by means of which the enzyme increases its selectivity for protein substrates (Schulman et al, 1998;Chantalat et al, 1999). We also demonstrated that the region encompassing amino acids 123-200 of CDC25B contains the binding site for CK2b.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…For p53, the binding region includes the sequence between amino acids 71-149, in the case of DNA Topoisomerase IIa a central region (amino acids 51-110) was implicated and for Nopp 140, the first Nterminal 20 amino acids. This diversity of docking sites on CK2b, which differ from the catalytic centre of the enzyme, may represent a mechanism by means of which the enzyme increases its selectivity for protein substrates (Schulman et al, 1998;Chantalat et al, 1999). We also demonstrated that the region encompassing amino acids 123-200 of CDC25B contains the binding site for CK2b.…”
Section: Discussionsupporting
confidence: 57%
“…Procedures for the expression and purification of GST-CK2a-HA (Heriche et al, 1997) MBP-CK2b (Chantalat et al, 1999) and GST-CK2b fusion proteins have been previously described. Purified proteins were separated on a 12% polyacrylamide gel and transferred to PVDF membranes.…”
Section: Mapping Of the Interaction Between Cdc25b And Ck2bmentioning
confidence: 99%
“…From a deletion study, we demonstrated that the N-terminal aa 1-55 represented the minimal region of CK2b for P1 peptide binding. This region, in the crystal structure of CK2b, is entirely a-helical (a1, a2, a3), extends at the surface of the molecule (Chantalat et al, 1999) and includes the putative destruction box and autophosphorylation sites (Litchfield, 2003). In agreement with the high-resolution structure of tetrameric CK2 (Niefind et al, 2001), the interaction of P1 with this region of CK2b neither dissociates the CK2 holoenzyme nor it prevents its formation.…”
Section: Discussionmentioning
confidence: 52%
“…The three-dimensional structure of the CK2b dimer has revealed the presence of solvent-exposed and -conserved residues that may represent binding surfaces for the multiple protein ligands previously identified as CK2b partners (Chantalat et al, 1999;Grein et al, 1999;Filhol et al, 2004). The identification of important protein kinases including A-Raf, c-Mos, Chk1 and Chk2 (Guerra et al, 1999b(Guerra et al, , 2003Bjorling-Poulsen et al, 2005) that interact with CK2b in the absence of catalytic CK2 subunits strongly suggests that CK2b has functions distinct from CK2a (Bibby and Litchfield, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Results presented by several groups and obtained by the use of a variety of approaches, including X-ray crystallography, have determined that a dimer of the CK2 subunits forms the core of the CK2 tetramer (Chantalat et al, 1999;Sarno et al, 2000;Canton et al, 2001). …”
Section: Introductionmentioning
confidence: 99%